Ultrasonic welding of AZ31B magnesium alloy and pure copper: microstructure, mechanical properties and finite element analysis - Zhao, Dewang; Jiang, Chao; Zhao, Kunmin (Journal of materials research and technology, 2023)
Magnesium alloy, copper and other light alloys are widely used in aerospace, new energy vehicles, lightweight manufacturing and other fields due to their excellent mechanical properties, but the connection between light alloys has always been a challenge. Ultrasonic welding is an advanced manufacturing technology that can realize high-strength connection between heterogeneous light alloys. In this study, ultrasonic welding between AZ31B magnesium and pure copper are carried out. The fracture, microstructure and tensile properties of the joint are studied, and its connection mechanism is analyzed. The finite element analysis model of magnesium-copper ultrasonic welding process is established. The fracture mode of magnesium-copper ultrasonic welded joint is interface-type fracture. The joint strength reaches the maximum value of 3798 N. The ultrasonic connection between magnesium alloy and copper is mainly realized by the interface diffusion layer formed in the welding process. The main component of the interface diffusion layer is Mg2Cu. The growth trend of interface diffusion layer is revealed. During welding, heat is generated in the central area of the solder joint, and then transferred around. The maximum temperature at the interface can reach 550 °C. The distribution law of temperature field and plastic deformation field of joint are revealed.